P225 Impact of Inflammatory Bowel Diseases on patients working life. (27th May 2021) - Sahar, N; Dahmani, W; Nour, E; Aya, H; Wafa, B A; Aida, B S; Salem, A; Ahlem, B; Mehdi, K; Hanene, J; Ali, J
Abstract: Background: Inflammatory bowel diseases (IBD) are a group of chronic disabling gastrointestinal disorders, consisting mainly of Crohn's disease (CD) and ulcerative (UC). A substantial part of the burden of illness in these conditions relates to the functional impairment, particularly affecting the ability to work. The aims of this study were to determine the impact of IBD on the working life of patient and to identify factors associated with a decreased productivity at work in patients with IBD. Methods: A cross-sectional study carried out at the Gastroenterology department of Sahloul University Hospital (CHU) over a period of 6 months. Patients with IBD (CD or UC) who present to the outpatient clinic or are hospitalized in the ward or day hospital were included. A questionnaire drawn up on the basis of qualitative studies on this subject is used to collect data on the professional career, the characteristics of the position held, difficulties encountered at work on a daily basis.The questionnaire will be accompanied by the "Work Productivity and Activity Impairment" (WPAI) work productivity score. Results: Among the 82 patients included, 58 had Crohn disease (CD) and 24 had ulcerative colitis (UC). The sex ratio was 1.2 and the mean age of our patients was 33.5 ± 10.2 years. . The majority of UC patients had pancolic involvement (n = 18; 75%). Among the 58 patients followed for CD, 24 (41.4%) had anoperineallesions. Twenty-two patients (26.8%) had already undergone intestinal resection. Six patients (7.3%) were on prolonged sick leave. The majority of patients worked in the private sector (n = 68; 82.9%). Two patients (2.4%) had a fixed rate of work per night. No patient had a job requiring frequent travel. Sixty-two patients (75.6%) had a weekly hourly volume greater than 40 hours.In half of the cases, the discovery of the disease preceded the choice of a professional career; among the remaining patients, this choice was influenced by IBD in 4 cases (10, 5%). Sixteen patients (21.5%) had to skip work hours during the week preceding the interview. The average number of hours missed due to a specific IBD-related problem was 5 hours with extremes ranging from 3 to 10 hours per week. An overall decrease in productivity (BGP) greater than 50% was objectified in 16 patients (21%). The average rates of absenteeism, presenteeism and BGP were 10.49%, 71.25% and 74.14% respectively. The presence of anoperineallesions was the only variable associated with BGP (50% vs 13.3%; p = 0.044). Conclusion: The impact of IBD on professional activity appears to be significant and requires special attention from both the gastroenterologists and the occupational physicians.